2014
DOI: 10.1016/j.jclinepi.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Up-to-dateness of reviews is often neglected in overviews: a systematic review

Abstract: The issue of up-to-dateness when conducting overviews seems to be neglected by most authors of overviews. Authors should assess the quality of evidence, based on their included reviews first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 21 publications
0
79
0
Order By: Relevance
“…Of these, 36 were recovered from electronic database searches, 2 from handsearching, and 9 from references. Thirty‐one full text papers were considered for inclusion in the scoping review; 24 papers (Aromataris et al, ; Cochrane Comparing Multiple Interventions Methods Group, ; Aromataris et al, ; Baker et al, ; Becker and Oxman, ; Caird et al, ; Cochrane Comparing Multiple Interventions Methods Group, ; Conn and Coon Sells, ; Cooper and Koenka, ; Hartling et al, ; Hartling et al, ; Ioannidis, ; Li et al, ; Pieper et al, ; Pieper et al, ; Pieper et al, ; Piso et al, ; Santaguida et al, ; Smith et al, ; Thomson et al, ; Thomson et al, ; Pieper et al, ; Ryan et al, ; Yuan et al, ) reporting 22 guidelines or descriptive studies met the inclusion criteria (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 36 were recovered from electronic database searches, 2 from handsearching, and 9 from references. Thirty‐one full text papers were considered for inclusion in the scoping review; 24 papers (Aromataris et al, ; Cochrane Comparing Multiple Interventions Methods Group, ; Aromataris et al, ; Baker et al, ; Becker and Oxman, ; Caird et al, ; Cochrane Comparing Multiple Interventions Methods Group, ; Conn and Coon Sells, ; Cooper and Koenka, ; Hartling et al, ; Hartling et al, ; Ioannidis, ; Li et al, ; Pieper et al, ; Pieper et al, ; Pieper et al, ; Piso et al, ; Santaguida et al, ; Smith et al, ; Thomson et al, ; Thomson et al, ; Pieper et al, ; Ryan et al, ; Yuan et al, ) reporting 22 guidelines or descriptive studies met the inclusion criteria (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the papers included in the scoping review, six described four sets of methodological guidelines assembled by a working group or editorial team (Aromataris et al, ; Aromataris et al, ; Becker and Oxman, ; Cochrane Comparing Multiple Interventions Methods Group, ; Conn and Coon Sells, ; Cochrane Comparing Multiple Interventions Methods Group, ); 10 were narrative reviews or descriptions of authors' anecdotal experiences conducting overviews (Baker et al, ; Caird et al, ; Cooper and Koenka, ; Hartling et al, ; Ioannidis, ; Santaguida et al, ; Smith et al, ; Thomson et al, ; Piso et al, ; Ryan et al, ); seven were systematic reviews in which authors used a pre‐specified, comprehensive search strategy to assemble all overviews published during a given date range in order to describe their methodological characteristics and reporting (Hartling et al, ; Li et al, ; Pieper et al, ; Pieper et al, ; Pieper et al, ; Thomson et al, ; Yuan et al, ); and one was a systematic review of HTA guidelines (Pieper et al, ). Papers are listed by type in Table and the objective and methodological issues addressed by each summarized.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly state plans for action to be taken if identified systematic review evidence is out of date or gaps in the evidence (i.e. absence of reviews) are identified) [56]. If searching for primary studies is to be considered, full details of the scope and methods for this should be provided.…”
Section: Resultsmentioning
confidence: 99%
“…Consider contacting authors of original reviews to see if they would update this. Note: Pieper [25] proposes and discusses two different approaches for searching for primary studies to ensure an overview is up-to-date; one approach involves searching for reviews and primary studies in parallel, whilst the other approach involves identifying the most up-to-date review and updating the searches from the date of the last search [56]. A clearly defined selection criteria for included reviews.The parameters or domains which are defined reflect the aims/focus of the overview.7.…”
Section: Resultsmentioning
confidence: 99%
“…Shortcomings of our umbrella review are that we did not investigate overlap between eligible systematic reviews or search for relevant RCTs not included by the reviews. Whether reviews are contemporary (‘up-to-date’) is often neglected in overviews [91], but the risk of bias to our own is small, with the Paton review of RCTs itself so recently conducted [26]. However, overlap of included studies between systematic reviews of ERAS packages has been shown to be substantial for colorectal surgery [26].…”
Section: Discussionmentioning
confidence: 99%